Evaluation of safety at work in a psychiatric setting: the "Workplace Safety Assessment" - Palumbo, Claudia; Di Sciascio, Guido; Distaso, Salvatore; Carabellese, Felice; Valerio, Antonella; Catanesi, Roberto (La Medicina del Lavoro, 2016)
Objectives: Workplace violence is a common risk for mental health professionals, and psychiatrists often encounter it in a variety of settings. The aim of this study was to estimate the prevalence and features of violent episodes toward psychiatrists in various mental healthcare system settings. Methods: All psychiatrists from the Region of Puglia (Apulia) were contacted (N=285) via email and were administered an on-line standardized questionnaire. Results: The response rate by psychiatrists was 57%. The main types of violence revealed were “threats” and “verbal aggression” and, of particular importance, “stalking”. Female psychiatrists seemed to be at a higher risk of becoming victims of workplace violence, especially as regards verbal abuse (OR: 2.7, 95% CI: 1.2-6.5, c2 6.7, p=0.0095) and reported more serious psychological consequences with need for rest after the episode of aggression. Conclusions: Our data confirm that mental health workers, particularly psychiatrists, are healthcare professionals at high risk for workplace violence. Future implementation of preventive strategies with the aim of reducing aggressive episodes towards psychiatrists should be a high priority for managers and policy-makers operating in the Italian healthcare sector.